2018
DOI: 10.1016/j.cmi.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trends of HIV drug resistance in a large Canadian cohort, 1996–2016

Abstract: HIV drug resistance transitioned from being primarily selected de-novo to being driven by TDR. Among those who started treatment in the past 5 years, ADR is rare and observed mostly in the lowest adherence strata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 27 publications
8
39
2
Order By: Relevance
“…Azidothymidine (AZT), lamivudine (3TC), and tenofovir (TDF), as rst-line NRTI drugs in China, have meager rates of transmission resistance (0.3%, 0.15%, and 0%, respectively). However, unlike the ndings reported in other studies, [4,5,[36][37][38][39][40] NRTI resistance showed the most signi cant increase (from 0% to 5.17%) from 2009 to 2017 in this study. Although the prevalence of TDR to PIs (0.44%) was signi cantly lower than the prevalence of TDR to NNRTIs/NRTIs, the I54M mutation caused universal resistance to PI drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…Azidothymidine (AZT), lamivudine (3TC), and tenofovir (TDF), as rst-line NRTI drugs in China, have meager rates of transmission resistance (0.3%, 0.15%, and 0%, respectively). However, unlike the ndings reported in other studies, [4,5,[36][37][38][39][40] NRTI resistance showed the most signi cant increase (from 0% to 5.17%) from 2009 to 2017 in this study. Although the prevalence of TDR to PIs (0.44%) was signi cantly lower than the prevalence of TDR to NNRTIs/NRTIs, the I54M mutation caused universal resistance to PI drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…This is likely due to multiple factors, potentially including patient management, cohort-wide adherence, and improvements in regimens resulting in greater genetic barriers to resistance. Research expanding upon this finding has recently been published, but more work is required to determine causation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…NNRTIs, or "non-nukes," had a different mode of action than other reverse transcriptase inhibitors then available, and triple reverse transcriptase-inhibitor therapy became an alternative to the existing PIbased treatments. In the 2000s and 2010s, NNRTIbased therapy became a very common HIV treatment (Rocheleau et al, 2018), but like all previous treatments, the NNRTI-based treatments were not evolution-proof. In a study published in 2009 (Hoffmann et al, 2009), Hoffman and colleagues followed South African patients treated with one of two common NNRTI-based regimens: zidovudine (AZT)+ 3TC + efavirenz (EFV) (95% of patients) or AZT + 3TC + nevirapine (NVP) (5% of patients).…”
Section: Order Of Resistance Mutations On Protease Inhibitor-based Trmentioning
confidence: 99%
“…Indeed, we argue that what actually happened in the years following the introduction of triple-drug cocktails represents an enduring mystery, one that has been in plain sight this whole time. Resistance rates did fall, but each year, a substantial number of patients on triple-drug therapy continued to develop drug resistance (Lee et al, 2014;Rocheleau et al, 2018).…”
Section: Introductionmentioning
confidence: 99%